The Hollywood Undead: Zombies Interpreted Scientifically - Ahn, Rebecca; Iweka, Chinyere (Journal of Student Research, 2023)
Modern media is fascinated by the undead. Zombie movies and shows comprise an entire genre by themselves, and there are many different renditions of the creatures in pop culture. This review was performed with the goal of analyzing the characteristics of zombies from The Walking Dead. This is organized around four major topics: organization of the biological hierarchy, energy and matter, interactions between systems, and evolution. These are the unifying principles of biology, and thus appropriate for assessing the biological principles behind zombie physiology. This review aims to show that some common features of zombies are simply exaggerations of preexisting human functions, and that they are not so removed from what we perceive as normal human behavior.